2010
DOI: 10.4066/amj.2010.345
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset and clinical presentation of urolithiasis in Ajman, UAE

Abstract: BackgroundUrolithiasis is an increasing problem in the United Arab Emirates (UAE). The mean age at onset of urolithiasis varies according to region. MethodRecords of urolithiasis cases confirmed by ultrasonography during the period 2007 to 2009 were retrieved from the Department of Medical Records. PASW 17 version was used for data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Kidney acts as a first barrier filter for crystals, thereby damaging tubular epithelium, which acts as a nidus for the stone formation. However, our result was different from the study of Venkatramana who observed the increased frequency of ureteric stone [ 32 ]. This variation might be due to selection of the patients irrespective of site of the stones.…”
Section: Discussioncontrasting
confidence: 99%
“…Kidney acts as a first barrier filter for crystals, thereby damaging tubular epithelium, which acts as a nidus for the stone formation. However, our result was different from the study of Venkatramana who observed the increased frequency of ureteric stone [ 32 ]. This variation might be due to selection of the patients irrespective of site of the stones.…”
Section: Discussioncontrasting
confidence: 99%
“…This can be caused by several factors, including lack of fluid consumption and weather, where the productive age group is required to keep on activities in hot weather. 10 Vigilance against urinary tract infections in this age group can accelerate the diagnosis of disease, especially in patients with unspecific complaints fever.…”
Section: Figure 1 the Distribution Number Of Patient Visits With Urogenital Disordersmentioning
confidence: 99%
“…Despite urolithiasis is a multifactorial disease, the study of the propensity towards the crystallization of stone forming salts in urine still remains the easiest strategy for the urologist to estimate the propensity towards the relapses of stone disease in individual patients [3]. In this paper, we described the biochemical analysis of the stones done in cases operated for urolithiasis in our institute [4] Objective: To study and determine the composition of stones by biochemical analysis in cases of urinary tract calculus.…”
Section: Introductionmentioning
confidence: 99%